Composite material as well as preparation method and application thereof
By mixing Zn0.4CuInS2 quantum dot powder with P25 TiO2 nanoparticles and TiO2 nanowires, composite materials are prepared, which solves the technical difficulties of improving photodetector performance, achieves higher responsiveness and detection rate, and reduces photoelectricity Detector fall time.
Patent Information
- Application Number
- CN202411028172.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-20
AI Technical Summary
It is difficult to prepare composite materials that can improve the photodetection performance of photodetectors through TiO2 nanowires, TiO2 nanoparticles and quantum dots.
Zn0.4CuInS2 quantum dot powder was dissolved in dichloromethane and mixed with P25 TiO2 nanoparticles and TiO2 nanowires, heated and stirred in a 40-45°C water bath environment, and then added dichloromethane to centrifuge to prepare the composite material. The amount of TiO2 nanowires added accounts for 10%-90% of the total mass, and the amount of Zn0.4CuInS2 quantum dot powder added is 25%-30%.
The composite material significantly improves the responsiveness, detection rate and drop time of the photodetector. Especially when the ratio of TiO2 nanowires is 40%, the photodetector's performance is optimal, providing efficient electron transmission paths and sufficient light Absorb specific surface area.
Smart Images

Figure BNBR8HZORMND2US99VK3O36MXMADBHE0QD1IQUEX 
Figure GWRQRRETWERIHIDT4BYSGGAFLLSCQLF4YI2NNH3W 
Figure IIXGDFGODZITF12A414ODUGQQPCGUIRUMF55RQZ5
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a composite material and a preparation method and application thereof. Background Art
[0002] A photodetector is a sensor that uses the photoelectric effect to convert light signals into electrical signals. It is widely used in many fields such as military, national economy, communications, industrial automation, environmental monitoring, energy utilization, security and defense. The working principle of a photodetector is based on the photoelectric effect, that is, when light shines on certain materials, it causes a change in the conductivity of the material, thereby generating a current or voltage signal. This change can be used to detect and measure light signals.
[0003] In the process of exploring the preparation of high-performance photodetectors, TiO2 nanostructures and quantum dots have become the focus of research due to their superior optoelectronic properties and regulatory flexibility. TiO2 nanowires (NWs) provide excellent electron transmission paths due to their one-dimensional structure, while TiO2 nanoparticles can provide more light absorption sites and charge separation interfaces due to their large specific surface area. In addition, quantum dots, with their size-controllable characteristics and broadband spectral responsiveness, bring high sensitivity and tunable light response range to photodetectors.
[0004] How to use TiO2 nanowires, TiO2 nanoparticles and quantum dots to prepare composite materials that can improve the photoelectric detection performance of photodetectors is a technical problem that needs to be solved. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a composite material and its preparation method and application, and solve the technical problem in the prior art of how to use TiO2 nanowires, TiO2 nanoparticles and quantum dots to prepare a composite material that can improve the photoelectric detection performance of photodetectors.
[0006] In order to achieve the above technical objectives, the technical solution of the present invention provides a method for preparing a composite material, comprising the following steps: Zn 0.4 CuInS2 quantum dot powder is dissolved in dichloromethane, and then mixed with P25 TiO2 nanoparticles and TiO2 nanowires, and then heated and stirred in a 40-45°C water bath environment, and then dichloromethane is added and centrifuged to obtain the composite material.
[0007] In any embodiment, the added amount of the TiO2 nanowires accounts for 10%-90% of the total mass of the P25 TiO2 nanoparticles and the TiO2 nanowires.
[0008] In any embodiment, the Zn 0.4The addition amount of CuInS2 quantum dot powder is 25%-30% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires.
[0009] In any embodiment, the TiO2 nanowires are prepared by the following steps: TiO2 nanoparticles and sodium hydroxide are mixed for hydrothermal reaction to obtain a solid product, the solid product is immersed in hydrochloric acid, and then the immersed solid product is calcined from room temperature to 600-650°C at a heating rate of 15-20°C / min and kept warm to obtain the TiO2 nanowires.
[0010] In any embodiment, the hydrothermal reaction temperature is 180-220° C., and the time is 72-75 hours; and / or, the holding time at 600-650° C. is 150-160 min.
[0011] In any embodiment, the Zn 0.4 CuInS2 quantum dot powder is prepared by the following steps: Mix zinc acetate powder, octadecene and oleylamine, degas, and then heat to 120-130° C. and keep reacting to obtain a Zn source precursor solution; Mix sulfur powder and oleylamine, degas, and then heat to 90-100° C. and keep reacting to obtain a S source precursor solution; The Zn source precursor solution, In(OAc)3, CuI, oleylamine and octadecene are mixed, degassed, heated to 90-100°C in a nitrogen atmosphere and kept reacting, then vacuumed, heated to 160-170°C in a nitrogen atmosphere and injected with the S source precursor solution, and kept reacting to obtain the Zn 0.4 CuInS2 quantum dot powder.
[0012] In addition, the present invention also provides a composite material prepared by the above preparation method.
[0013] In addition, the present invention also proposes a composite material prepared by the above preparation method or an application of the above composite material in the preparation of a photoelectric detector device.
[0014] In any embodiment, the application comprises: The composite material, α-terpineol, ethyl cellulose and anhydrous ethanol are mixed, and then heated in a 40-45° C. water bath environment to obtain a composite material slurry; The composite material slurry is spin-coated on the surface of conductive glass and then dried to obtain the photoelectric detector device.
[0015] In any embodiment, the heating time in a 40-45°C water bath environment is 2-3 hours.
[0016] Compared with the prior art, the beneficial effects of the present invention include: 0.4 CuInS2 quantum dot powder is dissolved in dichloromethane, then mixed with P25 TiO2 nanoparticles and TiO2 nanowires, then heated and stirred in a 40-45°C water bath environment, and then dichloromethane is added and centrifuged to obtain the composite material, which can improve the photoelectric detection performance of the photodetector, especially improve its responsiveness, detection rate and decay time. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a TEM image of the Zn0.4CuInS2 quantum dots prepared in Example 1 of the present invention.
[0018] Figure 2 This is the SEM spectrum of the TiO2 nanowires prepared in Example 1 of the present invention.
[0019] Figure 3 is a TEM image of the NWs-4 sample prepared in Example 1 of the present invention.
[0020] Figure 4 This is the energy dispersive X-ray spectrum of the NWs-4 sample prepared in Example 1 of the present invention.
[0021] Figure 5 It curves of the photodetectors corresponding to a series of samples prepared in Example 1 and Comparative Example 1 of the present invention.
[0022] Figure 6 It curve of the photodetector corresponding to the NWs-4 composite material prepared in Example 1.
[0023] Figure 7 The response results of the corresponding photodetectors of the NWs-4 composite material and P25 TiO2 nanoparticles prepared in Example 1 under 450 nm, 520 nm, and 620 nm light sources; wherein, Figure 7 (a) is the response result of the photodetector corresponding to the NWs-4 composite material; Figure 7 (b) is the response result of the photodetector corresponding to P25 TiO2 nanoparticles. DETAILED DESCRIPTION
[0024] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0025] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0026] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0027] This specific embodiment provides a method for preparing a composite material, comprising the following steps: Zn 0.4 The CuInS2 quantum dot powder is dissolved in dichloromethane, and then mixed with P25 TiO2 nanoparticles and TiO2 nanowires, and then heated and stirred in a 40-45°C water bath environment, and then dichloromethane is added and centrifuged to obtain the composite material; the amount of the TiO2 nanowires added is 10%-90% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires; The TiO2 nanowires are prepared by the following steps: Mix TiO2 nanoparticles and sodium hydroxide for hydrothermal reaction to obtain a solid product, wherein the temperature of the hydrothermal reaction is 180-220°C and the time is 72-75 hours; soak the solid product in hydrochloric acid, and then calcine the soaked solid product from room temperature to 600-650°C at a heating rate of 15-20°C / min and keep the temperature for 150-160min to obtain TiO2 nanowires; The Zn 0.4 CuInS2 quantum dot powder is prepared by the following steps: Mix zinc acetate powder, octadecene and oleylamine, degas, and then heat to 120-130° C. and keep reacting to obtain a Zn source precursor solution; Mix sulfur powder and oleylamine, degas, and then heat to 90-100° C. and keep reacting to obtain a S source precursor solution; The Zn source precursor solution, In(OAc)3, CuI, oleylamine and octadecene are mixed, degassed, heated to 90-100°C in a nitrogen atmosphere and kept reacting, then vacuumed, heated to 160-170°C in a nitrogen atmosphere and injected with the S source precursor solution, and kept reacting to obtain the Zn 0.4 CuInS2 quantum dot powder.
[0028] This specific embodiment also provides a composite material, which is prepared by the above preparation method.
[0029] This specific embodiment also proposes the composite material obtained by the above preparation method or the application of the above composite material in the preparation of a photoelectric detector device, including: The composite material, α-terpineol, ethyl cellulose and anhydrous ethanol are mixed, and then heated in a water bath environment at 40-45° C. for 2-3 hours to obtain a composite material slurry; The composite material slurry is spin-coated on the surface of conductive glass and then dried to obtain the photoelectric detector device.
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0031] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.
[0032] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It is understandable that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.
[0033] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.
[0034] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0035] The cuprous iodide (CuI, 99.999%), zinc acetate (Zn (CH3COO)2, 99.999%), indium acetate (In(C2H3O2)3, 99.999%), sublimed sulfur (S, AR), oleylamine (C 18 H 37 N, 80-90%), octadecene (C 18 H 36 , 95%) were purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0036] This embodiment provides a composite material, which is prepared by the following steps: 1) Zn source precursor solution 0.22 g of zinc acetate powder (Zn(OAc)2), 8 ml of octadecene (ODE) and 2 ml of oleylamine (OAM) were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 130°C and maintained for 5 min. After the timing was over, the mixture was naturally cooled to room temperature and sealed for storage to obtain a Zn source precursor solution with a concentration of 0.1 mol / L.
[0037] 2) S source precursor solution 0.48 g of sulfur powder (S powder) and 10 ml of OAM were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 90 °C and maintained for 5 min. After the timing was over, the solution was naturally cooled to room temperature and sealed to obtain a 1.25 mol / L concentration of S source precursor solution.
[0038] 3) Zn-doped CuInS2 quantum dots Take 0.08mL of Zn source precursor solution, 58.39mgIn(OAc)3, 38mgCuI, 4ml oleylamine and 8ml octadecene and mix them in a three-necked flask. After triple degassing, remove oxygen and other gas impurities in the solution. Heat to 100℃ in a nitrogen atmosphere and keep it at this temperature for 5 minutes to ensure that the mixture is fully dissolved. Then, vacuumize again to remove possible impurities such as oxygen and water vapor in the reaction system. Under nitrogen atmosphere, increase the temperature to 170℃ and quickly inject 1ml of S source precursor solution. Then keep the reaction for 15 minutes. After the reaction is completed, cool it to room temperature, centrifuge, wash and dry it to finally obtain Zn 0.04 CuInS2 quantum dot material.
[0039] 4) Preparation of TiO2 nanowires Dissolve 0.5 g TiO2 nanoparticles in 30 mL of 10 mol / L sodium hydroxide, stir thoroughly to mix them evenly, and then transfer them to a high-pressure reactor for hydrothermal reaction at a temperature of 200 °C for 72 h. After natural cooling, a solid product is obtained. The solid product is washed with deionized water until neutral, and then soaked in 0.1 mol / L dilute hydrochloric acid for 12 h. Wash again until neutral and dry. Then, the soaked solid product is calcined from room temperature to 650 °C at a heating rate of 20 °C / min and kept warm for 150 min to obtain TiO2 nanowires.
[0040] 5) Preparation of composite materials Zn 0.4 CuInS2 quantum dot powder was dissolved in 5 ml of dichloromethane, and P25 TiO2 nanoparticles and TiO2 nanowires were added and heated and stirred in a 40 °C water bath for 2 hours to fully mix them. Then, 10 ml of dichloromethane was added and centrifuged to remove the unadsorbed quantum dots, and the composite material was obtained after drying. 0.4The addition amount of CuInS2 quantum dot powder is 25% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires; the addition amount of the TiO2 nanowires is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires, respectively. A total of 9 composite materials with different TiO2 nanowire addition amounts were prepared, and they were marked as NWs-1, NWs-2, NWs-3, NWs-4, NWs-5, NWs-6, NWs-7, NWs-8 and NWs-9, respectively.
[0041] The transmission electron microscope (TEM) image of the Zn0.4CuInS2 quantum dots prepared in this example is as follows: Figure 1 As shown, TEM is a microscope with high resolution and high magnification. The steps of preparing the TEM test sample in this embodiment are to take 300 microliters of the prepared oil phase quantum dot Zn0.4CuInS2 and add 5 ml of dichloromethane to dilute it, and then take 150 microliters after dilution and drop it on the copper mesh. The reason for the dilution is that too many quantum dots will cause serious agglomeration. Under the scale of 100 nm, the quantum dot group is observed as a whole. They appear as dispersed light and dark contrast point structures, indicating the collective state of quantum dots and their distribution on the surface of the carrier. Continue to zoom in to 50 nm, and the individual particles of quantum dots begin to become clear. The gaps between the particles can be identified, and the nearly circular or polygonal morphology of the particles begins to appear, providing preliminary information about the uniformity of the size of the quantum dots.
[0042] At the scale of 20 nm, the details of a single quantum dot are more significant. The fine texture of the particle surface can be observed. At a magnification of 10 nm, the lattice structure of each quantum dot becomes visible, and the lattice arrangement and crystal plane spacing can be directly measured. Images at 5nm and 2nm resolution show that the quantum dot lattice fringes are clear, the structure is complete, and it has good crystallinity. Through this image, a certain number of lattice fringe lengths are measured, and the lattice fringe spacing is calculated to be 0.32 nm. By comparing with the standard PDF card of CuInS2 (JCPDS No.027-0159), its crystal plane index can be determined to be (112).
[0043] Figure 2 The SEM image of the prepared TiO2 nanowires. Figure 2 (a) is a picture taken at a scale of 10 microns, showing that the TiO2 nanowires appear as a series of slender and neatly arranged nanowires. Figure 2 (b) At the 2-micron scale, the microscopic details of the TiO2 nanowires become clearer. These nanowires have a relatively uniform width, a smooth surface, and no agglomeration.
[0044] Figure 3 This is a TEM image of the NWs-4 sample. The images show different features at different scales. At the macroscopic scale of 0.5μm, the overall TiO2 nanostructure and the distribution of quantum dots are observed. The picture shows one end of a nanowire. The nanoparticles are partially attached to the surface of the TiO2 nanowire and partially aggregated. At the scale of 200 nm, the surface states of the three substances are clearer. The larger particles attached to the nanowires should be TiO2 nanoparticles, while the smaller dark spots are quantum dots. At the scales of 100 nm and 50 nm, the particle size of the quantum dots and their contact surfaces with the nanowires and nanoparticles can be distinguished, and the shape of the quantum dots is clearly visible. At the scale of 20 nm, the outline, size and distribution of the quantum dots are clear, the morphology of the nanowires and nanoparticles shows a highly localized feature, and the high resolution of TEM reflects the subtle surface details. At the 10 nm scale, it is possible to observe the lattice fringes of individual quantum dots and TiO2 nanostructures, with the measured lattice spacing of 0.353 nm corresponding to the (101) crystal plane of TiO2 and the lattice fringes of 0.323 nm corresponding to the (112) crystal plane of CuInS2.
[0045] Figure 4 Energy dispersive X-ray spectra of NWs-4 samples, characteristic X-ray peaks of various elements were detected from the samples. 0.4 The mixed sample of CuInS2 quantum dots shows peaks of all elements in the lower spectrum, including Zn, Cu, In, S, Ti and O. EDX analysis was combined with scanning imaging. The distribution of elements is shown as different colored areas in the spectrum. It can be seen that Ti and O are concentrated in the TiO2 nanowire area, and the outline of the nanowire is clear, proving the composition of the nanowire. At the same time, the distribution of Zn, Cu, In and S in the quantum dot area shows the composition and dispersion of the quantum dots. The element distribution in the TiO2 nanowire outline area at the interface between quantum dots and nanowires is intertwined and overlapped with the element distribution of quantum dots, indicating the interaction and combination between the two. The EDX results combined with TEM imaging show the clear outline of the TiO2 nanowires and the mixing of quantum dots. This combination of morphology and composition analysis provides intuitive evidence of the composite structure of the material.
[0046] This embodiment provides a composite material, which is prepared by the following steps: 1) Zn source precursor solution 0.22 g of zinc acetate powder (Zn(OAc)2), 8 ml of octadecene (ODE) and 2 ml of oleylamine (OAM) were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 120°C and maintained for 5 min. After the timing was over, the mixture was naturally cooled to room temperature and sealed to obtain a 0.1 mol / L concentration of Zn source precursor solution.
[0047] 2) S source precursor solution 0.48 g of sulfur powder (S powder) and 10 ml of OAM were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 100 °C and maintained for 5 min. After the timing was completed, the solution was naturally cooled to room temperature and sealed to obtain a 1.25 mol / L concentration of S source precursor solution.
[0048] 3) Zn-doped CuInS2 quantum dots Take 0.08mL of Zn source precursor solution, 58.39mgIn(OAc)3, 38mgCuI, 4ml oleylamine and 8ml octadecene and mix them in a three-necked flask. After triple degassing, remove oxygen and other gas impurities in the solution. Heat to 90℃ in a nitrogen atmosphere and keep it at this temperature for 5 minutes to ensure that the mixture is fully dissolved. Then, vacuumize again to remove possible impurities such as oxygen and water vapor in the reaction system. Under nitrogen atmosphere, increase the temperature to 160℃ and quickly inject 1ml of S source precursor solution. Then keep the reaction for 15 minutes. After the reaction is completed, cool it to room temperature, centrifuge, wash and dry it to finally obtain Zn 0.04 CuInS2 quantum dot material.
[0049] 4) Preparation of TiO2 nanowires Dissolve 0.5 g TiO2 nanoparticles in 30 mL of 10 mol / L sodium hydroxide, stir thoroughly to mix thoroughly, and then transfer to a high-pressure reactor for hydrothermal reaction at a temperature of 180 °C for 75 h. After natural cooling, a solid product is obtained. The solid product is washed with deionized water until neutral, and then soaked in 0.1 mol / L dilute hydrochloric acid for 12 h. Wash again until neutral and dry. Then, the soaked solid product is calcined from room temperature to 600 °C at a heating rate of 20 °C / min and kept warm for 160 min to obtain TiO2 nanowires.
[0050] 5) Preparation of composite materials Zn 0.4CuInS2 quantum dot powder was dissolved in 5 ml of dichloromethane, and P25 TiO2 nanoparticles and TiO2 nanowires were added and heated and stirred in a 40 °C water bath for 2 hours to fully mix them. Then, 10 ml of dichloromethane was added and centrifuged to remove the unadsorbed quantum dots, and the composite material was obtained after drying. 0.4 The added amount of CuInS2 quantum dot powder is 25% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires; the added amount of the TiO2 nanowires is 40% of the total mass of the P25TiO2 nanoparticles and TiO2 nanowires.
[0051] This embodiment provides a composite material, which is prepared by the following steps: 1) Zn source precursor solution 0.22 g of zinc acetate powder (Zn(OAc)2), 8 ml of octadecene (ODE) and 2 ml of oleylamine (OAM) were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 125°C and maintained for 5 min. After the timing was over, the mixture was naturally cooled to room temperature and sealed for storage to obtain a Zn source precursor solution with a concentration of 0.1 mol / L.
[0052] 2) S source precursor solution 0.48 g of sulfur powder (S powder) and 10 ml of OAM were mixed in a three-necked flask and subjected to triple degassing to remove oxygen and other gas impurities in the solution. Subsequently, the temperature was raised to 95°C and maintained for 5 min. After the timing was over, the solution was naturally cooled to room temperature and sealed to obtain a 1.25 mol / L concentration of S source precursor solution.
[0053] 3) Zn-doped CuInS2 quantum dots Take 0.08mL of Zn source precursor solution, 58.39mgIn(OAc)3, 38mgCuI, 4ml oleylamine and 8ml octadecene and mix them in a three-necked flask. After triple degassing, remove oxygen and other gas impurities in the solution. Heat to 95℃ in a nitrogen atmosphere and keep it at this temperature for 5 minutes to ensure that the mixture is fully dissolved. Then vacuum it again to remove possible impurities such as oxygen and water vapor in the reaction system. Under nitrogen atmosphere, raise the temperature to 165℃ and quickly inject 1ml of S source precursor solution. Then keep the reaction for 15 minutes. After the reaction is completed, cool it to room temperature, centrifuge, wash and dry it to finally obtain Zn 0.04 CuInS2 quantum dot material.
[0054] 4) Preparation of TiO2 nanowires Dissolve 0.5 g TiO2 nanoparticles in 30 mL of 10 mol / L sodium hydroxide, stir thoroughly to mix them evenly, and then transfer them to a high-pressure reactor for hydrothermal reaction at a temperature of 220 °C for 72 h. After natural cooling, a solid product is obtained. The solid product is washed with deionized water until neutral, and then soaked in 0.1 mol / L dilute hydrochloric acid for 12 h. Wash again until neutral and dry. Then, the soaked solid product is calcined from room temperature to 650 °C at a heating rate of 20 °C / min and kept warm for 155 min to obtain TiO2 nanowires.
[0055] 5) Preparation of composite materials Zn 0.4 CuInS2 quantum dot powder was dissolved in 5 ml of dichloromethane, and P25 TiO2 nanoparticles and TiO2 nanowires were added and heated and stirred in a 40 °C water bath for 2 hours to fully mix them. Then, 10 ml of dichloromethane was added and centrifuged to remove the unadsorbed quantum dots, and the composite material was obtained after drying. 0.4 The added amount of CuInS2 quantum dot powder is 25% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires; the added amount of the TiO2 nanowires is 40% of the total mass of the P25TiO2 nanoparticles and TiO2 nanowires.
[0056] Comparative Example 1 The difference between this comparative example and Example 1 is that P25 TiO2 nanoparticles are not added, but the amount of P25 TiO2 nanoparticles is replaced by the TiO2 nanowires prepared in Example 1. Steps 1) to 4) of the preparation method of the composite material are the same as those in Example 1, and step 5) is different. Specifically, 5) prepares the composite material Zn 0.4 CuInS2 quantum dot powder was dissolved in 5 ml of dichloromethane, and TiO2 nanowires were added and heated in a 40 °C water bath and stirred for 2 hours to fully mix, and then 10 ml of dichloromethane was added and centrifuged to remove the unadsorbed quantum dots, and the composite material was obtained after drying; wherein the Zn 0.4 The addition amount of CuInS2 quantum dot powder is 25% of the total mass of the TiO2 nanowires, and the obtained composite material is marked as NWs-10.
[0057] Comparative Example 2 The difference between this comparative example and Example 1 is that no TiO2 nanowires are added, but the amount of TiO2 nanowires prepared in Example 1 is replaced by P25 TiO2 nanoparticles. Steps 1) to 4) of the preparation method of the composite material are the same as those in Example 1, and step 5) is different. Specifically, 5) prepares the composite material Zn0.4 CuInS2 quantum dot powder was dissolved in 5 ml of dichloromethane, and P25 TiO2 nanoparticles were added and heated in a 40 °C water bath and stirred for 2 hours to fully mix, and then 10 ml of dichloromethane was added and centrifuged to remove the unadsorbed quantum dots, and the composite material was obtained after drying; wherein the Zn 0.4 The addition amount of CuInS2 quantum dot powder is 25% of the total mass of the TiO2 nanowires, and the obtained composite material is marked as ZCIS / TiO2.
[0058] Application Examples The nine composite materials prepared in Example 1, the NWs-10 prepared in Comparative Example 1, the ZCIS / TiO2 prepared in Comparative Example 2, and the P25 TiO2 nanoparticles alone were used to prepare a photodetector device, including: 0.25 g of one of the nine composite materials prepared in Example 1, or NWs-10 prepared in Comparative Example 1, or ZCIS / TiO2 prepared in Comparative Example 2, or single P25 TiO2 nanoparticles were mixed with 1.025 g of α-pinene alcohol, 0.13 g of ethyl cellulose, and 3 ml of anhydrous ethanol, respectively, and heated and stirred in a 40°C water bath for 24 hours to volatilize excess anhydrous ethanol, finally obtaining a composite material slurry corresponding to each material; The prepared composite material slurry was spin-coated on the surface of conductive glass (20*10 mm, square resistance <7Ω, channel size 1*10 mm) at a speed of 3000 r / min, and then dried in a 50 ℃ drying oven to obtain a composite material photodetector device with a coating thickness of 3 μm.
[0059] Figure 5 A series of It curves are presented, representing the performance of TiO2 nanowire and nanoparticle hybrid photodetectors with different TiO2 nanowire ratios. As the proportion of TiO2 nanowires changes, a significant change in photocurrent is observed, which reflects the impact of different ratios on the performance of the detector. When the proportion of TiO2 nanowires reaches 40% (i.e., NWs-4 sample), the relevant It curve shows the highest photocurrent peak under illumination conditions. This shows that at this ratio, the performance of the photodetector is optimized and higher photoelectric conversion efficiency can be achieved. This is because TiO2 nanowires provide an efficient electron transfer path, while their combination with nanoparticles maintains sufficient specific surface area to facilitate light absorption and carrier generation. Figure 5(b) is the IV curve of different TiO2 nanowire ratios. As the voltage increases, the photocurrent generated by the NWs-4 sample device always remains at the highest level, showing good photoelectric conversion and carrier transport capabilities. This phenomenon is attributed to the better structural configuration of the device with 40% nanowire content, which not only ensures efficient charge separation but also promotes rapid charge transport. At the same time, this ratio provides the most ideal interface between TiO2 nanowires and nanoparticles, thereby improving the photodetection performance.
[0060] Table 1 Detailed photoelectric performance parameters of P25 TiO2 nanoparticles, ZCIS / TiO2 and NWs-4 photodetectors Sample TiO2 ZCIS / TiO2 NWs-4 Photocurrent(A) 1.50×10-9 2.60×10-7 7.94×10-6 Dark current(A) 8.15×10-14 1.20×10-11 1.06×10-11 Effective area (cm2) 0.75 0.725 0.3 Responsivity (A / W) 1.63×10-7 2.93×10-5 2.16×10-3 Detection rate (Jones) 8.76×108 1.27×1010 6.45×1011 Light-to-dark current ratio 1.84×104 2.17×104 7.53×105 Rise time Tr (s) 6.28 2.92 3.99 Fall time Td (s) 1.65 1.45 0.92 Table 1 shows that the response rate and detection rate of the NWs-4 photodetector are obviously higher than those of the P25 TiO2 nanoparticles and ZCIS / TiO2 photodetectors. In addition, the fall time of the NWs-4 photodetector is only 0.92s, which is also significantly lower than the fall time of the P25 TiO2 nanoparticles and ZCIS / TiO2 photodetectors. It should be noted that the composite materials prepared in Examples 2-3 have photodetection performance comparable to that of the NWs-4 composite materials prepared in Example 1.
[0061] Figure 6 The It curve of the photodetector corresponding to the NWs-4 composite material prepared in Example 1 has good repeatability. In the NWs-4 composite photodetector, the response rise time is 3.99 seconds, and the response recovery time is 0.92 seconds. In simple terms, this means that when the detector is stimulated by a light signal from a non-excited state and reaches a response saturation state, it takes 3.99 seconds. At the same time, when the light source is removed, the detector takes 0.92 seconds to return to the initial non-excited state.
[0062] The introduction of TiO2 nanowires provides an excellent electron transmission path and improves the photoelectric detection performance of the original material. Under a 365 nm light source, the responsivity of the NWs-4 composite thin film photodetector is 2.16×10 -3 A / W, detection rate is 6.45×10 11 Jones, the response time is 3.99 s and the response recovery time is 0.92 s.
[0063] Combination Figure 7 The composite material NWs-4 photodetector prepared by the present invention exhibits excellent responsivity and detection rate under 450 nm, 520 nm and 620 nm light sources. The composite material greatly broadens the light response range of the original TiO2 photodetector, and its repeatability and stability are relatively excellent.
[0064] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite material, characterized in that: The following steps are involved: Zn 0.4 CuInS2 quantum dot powder is dissolved in dichloromethane, and then mixed with P25 TiO2 nanoparticles and TiO2 nanowires, and then heated and stirred in a 40-45°C water bath environment, and then dichloromethane is added and centrifuged to obtain the composite material.
2. The method for preparing a composite material according to claim 1, characterized in that: The added amount of the TiO2 nanowires accounts for 10%-90% of the total mass of the P25 TiO2 nanoparticles and the TiO2 nanowires.
3. The method for preparing a composite material according to claim 1, characterized in that: The Zn 0.4 The addition amount of CuInS2 quantum dot powder is 25%-30% of the total mass of the P25 TiO2 nanoparticles and TiO2 nanowires.
4. The method for preparing a composite material according to claim 1, characterized in that: The TiO2 nanowires are prepared by the following steps: TiO2 nanoparticles and sodium hydroxide are mixed for hydrothermal reaction to obtain a solid product, the solid product is immersed in hydrochloric acid, and then the immersed solid product is calcined from room temperature to 600-650°C at a heating rate of 15-20°C / min and kept warm to obtain the TiO2 nanowires.
5. The method for preparing a composite material according to claim 4, characterized in that: The hydrothermal reaction temperature is 180-220° C., and the time is 72-75 hours; and / or, the heat preservation time at 600-650° C. is 150-160 minutes.
6. The method for preparing a composite material according to claim 3, characterized in that: The Zn 0.4 CuInS2 quantum dot powder is prepared by the following steps: Mix zinc acetate powder, octadecene and oleylamine, degas, and then heat to 120-130° C. and keep reacting to obtain a Zn source precursor solution; Mix sulfur powder and oleylamine, degas, and then heat to 90-100° C. and keep reacting to obtain a S source precursor solution; The Zn source precursor solution, In(OAc)3, CuI, oleylamine and octadecene are mixed, degassed, heated to 90-100°C in a nitrogen atmosphere and kept reacting, then vacuumed, heated to 160-170°C in a nitrogen atmosphere and injected with the S source precursor solution, and kept reacting to obtain the Zn 0.4 CuInS2 quantum dot powder.
7. A composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the composite material obtained by the preparation method according to any one of claims 1 to 6 or the composite material according to claim 7 in the preparation of a photodetector device.
9. The use according to claim 8, comprising: The composite material, α-terpineol, ethyl cellulose and anhydrous ethanol are mixed, and then heated in a 40-45° C. water bath environment to obtain a composite material slurry; The composite material slurry is spin-coated on the surface of conductive glass and then dried to obtain the photoelectric detector device.
10. The use according to claim 9, characterized in that: The heating time in a 40-45°C water bath environment is 2-3 hours.
Citation Information
Patent Citations
Method for improving photoelectrochemical performance of copper indium sulfide / titanium oxide heterojunction nanorod array composite material through metal ion doping
CN115888762A
